ANALYSIS OF CHANGES IN THE CONCEPTION OF PROSPECTIVE PHYSICS TEACHER STUDENTS IN USING CONCEPTUAL CHANGE TEXTS ON THE TOPIC OF LIGHT INTERFERENCE - A. Sri Astika Wahyuni; Andi Muhammad Irfan; Usman Usman (Universitas Negeri Makassar, 2024)
This research is a type of quantitative descriptive research that aims to describe the conceptual changes of prospective physics teacher students on the topic of light interference after the application of the Conceptual Change Text. The steps taken are 1) Observation and definition, 2) designing the Conceptual Change Text, 3) collecting student conceptions, 4) applying the Conceptual Change Text in learning, 5) data analysis, and 6) interpretation of student conceptual change data. The subjects of this study were 35 prospective physics teacher students who were programming the Basic Physics course. The results of this study indicate that in the concept of the conditions for the process of light interference are 80% experienced construction and 56% experienced reconstruction; the concept of constructive-destructive interference obtained 82% who experienced construction and 88% who experienced reconstruction; and in the concept of interference in thin layers defined 67% experienced construction and 54% who experienced reconstruction. It can be concluded that most prospective subject teachers with different initial conceptions can achieve deep and complete conceptual understanding through the process of construction (having no conception to becoming a scientific conception) and reconstruction (misconception to becoming a scientific conception) through the Conceptual Change Text.